Hubungan Tingkat Religiusitas, Tingkat Kebersyukuran dengan Kejadian Depresi pada Remaja - Jabir, M.Agus; Pawirowiyono, Akemat; Imelisa, Rahmi; Yosep, Iyus; Wisnusakti, Khrisna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between the level of religiosity, the level of gratitude, and the incidence of depression in teenagers in high schools in Labakkang District, Pangkep Regency. The research method used is a cross-sectional method. The results of the study showed that the highest level of religiosity was 98.5%, moderate level of gratitude was 97%, and no depression was 98.5%. Of the 200 respondents who had a high level of religiosity, 200 (100.0%) also did not experience depression, while 3 respondents had a moderate level of religiosity, as many as 3 (100.0%). Meanwhile, the relationship between gratitude and the incidence of depression shows that of the 197 respondents who had a moderate level of gratitude, 3 (1.5%) experienced mild depression, while of the 6 respondents who had a high level of gratitude, 6 (100.0%) did not experience depression. In conclusion, there is a relationship between the level of religiosity and the incidence of depression, and there is no relationship between the level of gratitude and the incidence of depression. Keywords: Depression, Gratitude, Religiosity